THE ENGLISH PROFICIENCY OF TOURIST ACTORS IN KLATEN - Umi Sholihah; Didik Rinan Sumekto (Lingua, 2021)
This study aims to know the English proficiency of tourist actors in Klaten. The data of this research consist of primary data and secondary data. Primary data are the data gotten from English proficiency of tourist actors in Klaten, especially in speaking skill. Meanwhile, secondary data are the data from the tourism department of Klaten. This research method is descriptive quantitative. The subjects of this study are tourist actors in temple and water tourist spots in Klaten, which consists of officers, sellers, parking attendants, security, and other tourist actors. The temple tourist spots are Plaosan temple and Sojiwan temple. Meanwhile, the water tourist spots are Umbul Ponggok and Umbul Cokro (OMAC). The choice of those spots is depended on the most foreign tourists among that type of tourist destinations. The result of the study shows that the English proficiency of tourist actors in temple tourist attractions is higher (50%) than water tourist attractions (8,33%). In temple tourist attractions, tourist actors who have high English proficiency is 50%, average is 37.5%, low is 12.5%. In water tourist attractions, tourist actors who have high English proficiency is 8.33%, average is 29.16%, low is 62.5%. This study also got other data that tourist actors in Klaten have important role to support tourism industry in Klaten to attract tourists, both domestic and foreign, but their awareness of it is still low. Most of them still rely on domestic tourists than foreigners.